SOSIALISASI UPAYA PENINGKATAN PENJUALAN BAGI UMKM MELALUI STRATEGI BRANDING PADA PELAKU UMKM DI PANTAI KUTA DESA KUTA KECAMATAN PUJUT KABUPATEN LOMBOK TENGAH - Yuliandari, Rini; Suharti, Suharti; Permadi, I Gusti Agung Didit Eka; Alifianti, Anggun Sukma; Rahmadani, Ceila (LPPM Institut Pendidikan Nusantara Global, 2024)
Micro, Small and Medium Enterprises (MSMEs) are a reliable driver of the economy and their existence is highly regarded. MSMEs contribute quite a lot to the Indonesia economy, especially in Kuta Beach which is located in Central Lombok Regency, Lombok Island, they can absorb labor thereby reducing labor problems in Central Lombok Regency, plus there is the largest tourist destination on Lombok Island which is located on Kuta Beach. If we look further into each organ of the MSME body, there are still many problems and shortcomings. They are many problems faced by MSMEs in the continuity of their business, especially from understanding MSME development strategies. This community service aims to find whether out whether MSMEs carry out strategic management well, especially in developing MSMEs to run their businesses and whether MSMEs understand development methods and strategies well. The aim of implementing this Community Service Activity (PKM) is to help socialize branding strategies as an effort to increase sales for MSMEs. This PKM activity was carried out in the Kuta Beach area, Central Lombok. The implementation method for this activity is to provide material related to branding strategies through the use of digital technology. The conclusion obtained from the results of this PKM activity is that the assistance activities for business actors regarding brand identity have been carried out well. Mentoring activities are carried out by introducing, strengthening and increasing the understanding of PKM participants through branding strategies using brand identity.